Population of Anabas testudineus of the Lubuk Siam Lake, Lubuk Siam Village, Siak Hulu Sub-District Riau Province - Ade Novia Felni; M. Fauzi M. Fauzi; Nur El Fajri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT Betok fish is one type of species that is influenced by the season and lives in the Lubuk Siam Lake. A research aimed to understand the standing Stock of Anabas testudineus in size distribution of fish caught in Lubuk Siam Lake. Fish was sampled in 3 sampling points using nets and traps. The research was conducted in April-May 2019. The Standing Stock was analyzed based on Leslie method. The results shown that the initial population (No) of the fish was 450 kg and the final population (Nt) was 438 kg, temperature was 27-28, clarity was 62-93 cm, and pH=6.Keywords: Leslie method, Oxbow lake, Maximum captured, Fish population